Two new isoflavones from the tubers of Apios taiwanianus. (March 2016) - Lin, Chwan-Fwu; Liu, Yen-Wenn; Kuo, Yueh-Hsiung; Shen, Chien-Chang; Chiou, Wen-Fei; Chen, Chien-Chih
Graphical abstract: Highlights: We investigate the phytochemical composition of Apios taiwanianus . Twenty compounds were isolated from tubers of A. taiwanianus . Two new isoflavones, apioisoflavone (2) and isoapioisoflavone (3) were isolated. This is the first phytochemical study on A. taiwanianus . Lupinalbin A (6) and dephnoretin (11) showed osteogenic effects in MC3T3-E1 cells. Abstract: Apios taiwanianus is a medicinal plant in Taiwan. The tuber of A. taiwanianus is used as a folk medicine to treat hyperthyroidism, herpes, and tumors. We carried out the phytochemical study of A. taiwanianus . Two new isoflavones, apioisoflavone (2 ) and isoapioisoflavone (3 ), along with eighteen known compounds were isolated from the tubers of A. taiwanianus . The structures of these compounds were determined by spectral analyses and comparison with those in the literature. Compounds lupinalbin A (6 ) and dephnoretin (11 ) were shown to enhance the alkaline phosphatase (ALP) activity in MC3T3-E1 osteoblasts.